Financial literacy among university students in ghana - Asihene Amponsah Edith (KNUST, 2024)
A thesis submitted to the department of accounting and finance, school of business, kwame nkrumah university of science and technology, in partial fulfillment of the requirements for the award of the degree of master of business administration (finance)